A Case of QT Prolongation Associated with Panhypopituitarism - Dilek Arpaci; Mustafa Volkan Demir; Tayfun Garip; Ali Tamer (Case Reports in Endocrinology)
We describe a 37-year-old patient with panhypopituitarism who experienced symptoms and signs of hormonal insufficiency and QT prolongation on electrocardiogram without electrolyte disturbances. After hormonal (steroidal and thyroid) replacement therapy electrocardiographic findings were normalized. Hormonal disorders should be considered as a cause of long QT intervals which may lead to torsade de pointes, even if plasma electrolyte levels are normal, because life-threatening arrhythmia is treatable by supplementation of the hormone that is lacking.